Peripheral metabolic alterations associated with pathological manifestations of Parkinson’s disease in gut-brain axis-based mouse model - Huh, Eugene; Choi, Jin Gyu; Lee, Mee Youn; Kim, Jin Hee; Choi, Yujin; Ju, In Gyoung; Eo, Hyeyoon; Park, Myoung Gyu; Kim, Dong-Hyun; Park, Hi-Joon; Lee, Choong Hwan; Oh, Myung Sook (Frontiers in Molecular Neuroscience, 2023)
Parkinson’s disease (PD) is a representative neurodegenerative disease, and its diagnosis relies on the evaluation of clinical manifestations or brain neuroimaging in the absence of a crucial noninvasive biomarker. Here, we used non-targeted metabolomics profiling to identify metabolic alterations in the colon and plasma samples of Proteus mirabilis (P.mirabilis)-treated mice, which is a possible animal model for investigating the microbiota-gut-brain axis. We performed gas chromatography-mass spectrometry to analyze the samples and detected metabolites that could reflect P.mirabilis-induced disease progression and pathology. Pattern, correlation and pathway enrichment analyses showed significant alterations in sugar metabolism such as galactose metabolism and fructose and mannose metabolism, which are closely associated with energy metabolism and lipid metabolism. This study indicates possible metabolic factors for P.mirabilis-induced pathological progression and provides evidence of metabolic alterations associated with P.mirabilis-mediated pathology of brain neurodegeneration.